Em busca de um lugar: narrativas de deslocamentos e re-localizações, nos romances Rakushisha, Azul corvo e Hanói, de Adriana Lisboa - Vander Vieira de Resende (2020)
Displacements outside of the nation have represented a constant theme in Brazilian literature. Expanded in the first two decades of the 21st century, the representation of departures from Brazil has been related to the recrudescence of globalization, the crisis of the nation, the fragmentation of identities and the decentering of subjectivities. To analyze the complexity of such a strand of Brazilian literature, in this thesis were chosen narratives by contemporary writer Adriana Lisboa – Rakushisha (2007), Azul corvo (2010), Hanoi (2013). The objective is to investigate the peculiarities of these three novels regarding the representation of characters experiencing spatial, national, linguistic, identity, cultural, social, subjective, affective, displacements, themes dear to the so-called cultural studies, privileging theorists such as Sandra Almeida, Zygmunt Bauman, Homi Bhabha, Maria Zilda Cury, Stuart Hall, Gilles Lipovetsky, Silviano Santiago and others. We highlight the originality of Adriana Lisboa's production in the treatment given to these displacements narratives: the permanence of the nation in a time considered to be post-national; the presence of geocultural borders in a so-called world without borders; hostility towards displaced subjects; resistance to cultural hybridity; preferential transit to non-global cities; hospitality, solidarity and friendship among displaced subjects, in a context of hyper-individualism; the yearning for a return to a nuclear family; and the reiterated search for a place. In the midst of these ambivalent aspects, it is considered that although these are narratives of de-centerings and displacements, they are, at the same time, narratives of re-centerings and re-placements. In a globalized context, considered as unstable, liquid, of emptying of meanings and loss of references, Rakushisha, Azul Corvo and Hanói configure a poetics of dislocation and re-locations in which characters dislocated in the departed nation seek a place of stability and security to re-placed themselves.